Messages for railway systems based on 30 years' experience of Japanese national railway privatization - Yoshitaka Ishii; Kai Xu; K. E. Seetharam (Asian Development Bank Institute (ADBI), 2019)
The paper provides information for railway systems based on 30 years' experience of Japanese railway privatization. First, we introduce the background, framework, and result of the Japanese National Railway reform, especially from the perspective of the former president of the JR Kyushu Railway Company. We explain the challenges, such as diversified businesses and employee capacity building, that the company faced during that time and the creation of the business foundation in preparation for the transformation into a private company. We also discuss the tasks of the railway, including the freight transport of the high-speed railway (the Shinkansen logistics), as well as the population decline and aging society in Japan and their relationship with the railway system. Last, we summarize the implications of Japan's railway experience for a broader railway system. The high levels of safety and efficiency of Japan's railway system are based on the railway culture (hard, soft, heart) and the Japanese nationality. The railway system is extremely important for long-term economic development. In addition, we introduce the PPET Railway-ology, which integrates philosophy, politics, economy, and technology. The paper crystallizes years of railway experience and offers valuable lessons for the development of railway systems worldwide.
Keywords: R4; R41; 330; railway system; railway company privatization; JR Kyushu Railway Company